2012
DOI: 10.4103/0970-0218.94009
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion: An effective tool for global health

Abstract: Health promotion is very relevant today. There is a global acceptance that health and social wellbeing are determined by many factors outside the health system which include socioeconomic conditions, patterns of consumption associated with food and communication, demographic patterns, learning environments, family patterns, the cultural and social fabric of societies; sociopolitical and economic changes, including commercialization and trade and global environmental change. In such a situation, health issues c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
184
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(233 citation statements)
references
References 13 publications
1
184
0
14
Order By: Relevance
“…Health and wellbeing are not limited to the healthcare system (Kumar & Preetha, 2012). People’s living environments, their daily activities and their relationships are potentially creating stressors that affect people’s health and wellbeing.…”
Section: Resultsmentioning
confidence: 99%
“…Health and wellbeing are not limited to the healthcare system (Kumar & Preetha, 2012). People’s living environments, their daily activities and their relationships are potentially creating stressors that affect people’s health and wellbeing.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the proportion of health problems in a tested group significantly decreased over time and in general employees of the tested group always felt better. Similarly, some researchers indicated that overall well-being of participants was the most common effect of health promotions (Kumar & Preetha, 2012), even though the course and the interactions of agents are still a mystery. The health issues and the absenteeism variables were not correlated in this study and the average absence days caused by health problems increased in the tested group over time.…”
Section: Discussionmentioning
confidence: 99%
“…According to other researchers, cardiovascular nursing is important in different fields of health including primary, secondary and tertiary care. Therefore, these nurses should obtain skills and knowledge in four areas of health promotion, cardiac disease prevention and rehabilitation, acute, chronic and episodic care and palliative care (Kumar & Preetha, 2012). Care for the elderly with cardiovascular disease needs having cardiovascular knowledge, knowing how to train patients, performing health assessment, developing care plans, procedures to ensure the quality of care, etc.…”
Section: Discussionmentioning
confidence: 99%